Respuesta :

Here is the graph for the equation

Ver imagen noahpatchett0

Given function to be graphed is,

f(x) = (x - 2)(x - 6)

We will convert the equation of the function into the vertex form,

(x - 2)(x - 6) = x(x - 6) - 2(x - 6)

                  = x² - 6x - 2x + 12

                  = x² - 8x + 12

                  = x² - 2(4x) + 16 - 4

            f(x) = (x - 4)²- 4

By comparing this equation with the vertex form of the equation of a parabola,

g(x) = a(x - h)² + k

Here, (h, k) is the vertex of the parabola.

Therefore, vertex of the function 'f' will be (4, 4).

Now we will find the x-intercepts and y-intercept of the function.

For x-intercept, put f(x) = 0

0 = (x - 4)²- 4

(x - 4) = ±2

x = 4 ± 2

x = 2, 6

Therefore, x-intercepts of the function are (2, 0) and (6, 0).

For y-intercept, put x = 0

f(0) = (0 - 2)(0 - 6)

f(0) = 12

Therefore, y-intercept of the function is (0, 12).

By plotting these ordered pairs and joining them by a curve we can get the graph of the parabola.

Learn more how to graph a curve,

https://brainly.com/question/16180199

Ver imagen eudora
ACCESS MORE